Magnetoresistance and Anomalous Hall Effect of InSb Doped with Mn - A.V. Kochura; B.A. Aronzon; M. Alam; A. Lashkul; S.F. Marenkin; M.A. Shakhov; E.P. Kochura; E. Lahderanta (Журнал нано- та електронної фізики)
Transport properties of polycrystalline (In, Mn)Sb samples are investigated. Behavior of the temperature and magnetic field dependencies of the resistivity, anomalous Hall coefficient and magnetoresistivity at low temperatures points out the influence of Mn complexes, Mn ions and nano- and microsizes MnSb precipitates on charge transport.